Innovation in Health Care : Case Medical Helpline 116117 - Rajala, Marika (My University, 2021)
Innovations are becoming more and more important in the public sector than they have been before. There is a lot of expectation to reform public sector services and operations. Also, the challenges facing society seem to be even more complex and multidimensional. Innovation can be used to seek different kinds of solutions to these expectations and challenges. The objective of the public sector is of higher quality and more cost-effectively delivered public services for citizens. It is possible to find out innovative approaches to enhance operations, improve services´ productivity, and quality of offered services. The point of interest in this research is nationwide phone counseling and guidance service Medical Helpline 116117. Participants of this study were the primary health care and the special health care nursing staff in the hospital district of South Ostrobothnia. Medical Helpline 116117 was put into operation in December 2019 in the hospital district of South Ostrobothnia. This research aimed to find out how the nursing staff experiences the Medical Helpline 116117. There was also the possibility to find out if there are differences between special health care and primary health care. This research was also interested in the challenges and benefits of the Medical Helpline from a staff point of view. This research is quantitative research, and the empirical material gathered through a questionnaire. The questionnaire was executed by Webropol 3.0 online survey program in the common emergency service clinic at the hospital of Seinäjoki and in emergency duties at the health centers. The data was collected at the turn of March-April 2020. Based on the analysis of the empirical material, the Medical Helpline 116117 was seen positively, and the nursing staff´s opinion was that the Medical Helpline 116117 is a necessary service in health care. The Medical Helpline 116117 is a service/product innovation. The goal of such innovation is to change the way service is produced for a better outcome for customers, develop the quality of service, and make operations more efficient. The results showed that the right kind of changes has been made to the chain of services, as directing customers to the right places was found to be easier after the introduction of Medical Helpline 116117. According to nursing staff, Medical Helpline 116117 is customer-oriented, and it brings added value to customers. The results showed that it is important that the Medical Helpline 116117 is a round-a-clock service. In this way, customers get help, information, and instructions for their own situations regardless of the time of the day. This brings safety to customers. In particular, there was a decrease in unnecessary doctor visits in the common emergency clinic at the hospital, which supports the fact that the operational model of the hospital district has been able to be enhanced to a better direction because of the Medical Helpline 116117.

Innovaatiot ovat tulleet yhä tärkeämmäksi julkisella sektorilla. Julkisten palveluiden ja toimintojen uudistamista kohtaan liittyy paljon odotuksia. Myös yhteiskunnan kohtaamat haasteet ovat monimutkaisia ja moniulotteisia. Innovaatioiden avulla voidaan etsiä erilaisia ratkaisuja näihin odotuksiin ja haasteisiin. Julkisen sektorin tavoitteena on tuottaa kansalaisille korkealaatuisempia ja kustannustehokkaammin tuotettuja palveluita. On mahdollista löytää innovatiivisia lähestymistapoja toiminnan tehostamiseksi ja palveluiden tuottavuuden ja laadun parantamiseksi. Tämän tutkielman kohteena on valtakunnallinen ohjaus- ja neuvontapalvelu Päivystysapupuhelin 116117. Tutkimukseen osallistui erikoissairaanhoidon ja perusterveydenhuollon hoitohenkilöstöä Etelä-Pohjanmaan sairaanhoitopiirin alueelta. Päivystysapupuhelin 116117 otettiin käyttöön sairaanhoitopiirissä joulukuussa 2019. Tutkimuksen tarkoitus oli selvittää, miten hoitohenkilökunta on kokenut Päivystysapupuhelimen. Samalla oli mahdollisuus selvittää, esiintyykö erikoissairaanhoidon ja perusterveydenhuollon välillä eroja kokemusten suhteen. Tutkimuksessa selvitettiin myös hoitohenkilöstön kokemusten perusteella Päivystysapupuhelin 116117:n haasteita ja hyötyjä. Tämän määrällisen tutkimuksen empiirinen materiaali kerättiin Webropol-kyselytyökalun avulla tehdyllä kyselyllä erikoissairaanhoidon osalta Seinäjoen keskussairaalan yhteispäivystyksen ja perusterveydenhuollon osalta kiirevastaanottojen hoitohenkilökunnalta. Materiaali kerättiin maalis-huhtikuun vaihteessa 2020. Kerätyn materiaalin perusteella Päivystysapupuhelin nähdään positiivisena, ja hoitohenkilökunta kokee Päivystysapupuhelin 116117:n tarpeellisena palveluna. Päivystysapupuhelin 116117 on palvelu- ja tuoteinnovaatio. Tällaisen innovaation tavoitteena on muuttaa palvelun tuottamistapaa asiakkaiden kannalta parempaan lopputulokseen, kehittää palvelun laatua ja tehostaa toimintaa. Tulosten perusteella Päivystysapupuhelin on muuttanut terveydenhuollon palveluiden tarjontatapaa parempaan suuntaan, sillä hoitohenkilökunnan mielestä Päivystysapupuhelimen tultua asiakkaiden ohjaaminen oikeaan paikkaan on helpompaa. Kyselyn vastaajat olivat sitä mieltä, että Päivystysapupuhelin 116117 on asiakaslähtöinen ja tuo lisäarvoa asiakkaalle. Tuloksista nousi esiin myös Päivystysapupuhelimen tarjoaman ympärivuorokautisen palvelun tärkeys. Näin asiakas saa apua, tietoa ja ohjeita kellonajasta huolimatta. Tämä tuo turvallisuutta asiakkaille. Kyselyyn vastanneiden mukaan turhat lääkärikäynnit sairaalan yhteispäivystyksessä ovat vähentyneet, mikä tukee palvelun tuotantotavan muuttumista parempaan suuntaan.
Keywords: public sector; public health service; innovations; primary health care; health care; social innovations; special health care; fi=Julkisjohtaminen|en=Public Management|; fi=Hallintotieteiden maisteriohjelma|en=Master's Programme in Administrative Sciences|